Katalysatorscreening für die katalytische Spaltung von Braunkohle. Issue 4 (1st February 2013) - Seitz, Mathias; Nowak, Sascha; Welscher, Julia; Zimmermann, Jens; Nägler, Thomas; Stam‐Creutz, Timo; Frank, Willy; Schwieger, Wilhelm; Klemm, Elias; Greiner, Lasse; Horn, Raimund
<x xml:space="preserve">Abstract</x> Different processes were developed in the past to use lignite for chemical production. One of them is pyrolysis. In this work a new approach was investigated where the catalyst comes in contact directly with the lignite. Aliphatic components of the lignite can be cracked and olefins and aromatics can be formed. A catalyst screening shows that zeolites can be used for this purpose. A suitable catalyst with similar behavior can be crystallized on a carrier to improve the separation from coke residues.